Effect of Penta Herbs Forte on Antioxidant Capacity and Cardiac Protein Carbonyl Levels in a Hypoxia-Induced Rat Model - Sentanu Widiarto; Shirly Gunawan; David Limanan; Frans Ferdinal; Eny Yulianti (Biomedical Journal of Indonesia, 2026)
Introduction. Hypoxia, a state of inadequate oxygen supply in tissues, can induce the generation of reactive oxygen species (ROS), leading to oxidative stress and damage to biomolecules such as proteins. This damage can be quantified by measuring protein carbonyl levels. Penta Herbs Forte (PHF), a polyherbal formulation composed of Andrographis paniculata, Blumea balsamifera, Phyllanthus urinaria, Zingiber officinale, and Curcuma xanthorrhiza, is rich in bioactive compounds with known antioxidant properties. This study aimed to evaluate the antioxidant activity of PHF extract and its effects on cardiac protein carbonyl levels in hypoxia-induced rats. Methods. This experimental study included 32 male Sprague-Dawley rats, divided into eight groups: control and treatment groups under normoxia, 1-day hypoxia, 7-day hypoxia, and 14-day hypoxia, either with or without PHF extract administration. Antioxidant capacity was determined using the ABTS and DPPH assays, and cardiac protein carbonyl levels were measured using a spectrophotometer. Results. PHF extract showed an antioxidant activity yielding LC50 values of 22.135 μg/mL (ABTS) and 105.04 μg/mL (DPPH), indicating strong antioxidant potential. PHF-treated groups exhibited lower cardiac protein carbonyl levels than their respective controls across all hypoxic durations. Conclusion. Administration of PHF extract reduced cardiac protein carbonyl levels via its antioxidant activity, suggesting its potential as an exogenous antioxidant source to protect against hypoxia-induced oxidative damage.